2006
DOI: 10.1002/anie.200503195
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of the Macrolide‐Glycosylating Enzyme Pair DesVII/DesVIII: Opportunities, Limitations, and Mechanistic Hypotheses

Abstract: Two's Company: DesVII, a glycosyltransferase involved in the biosynthesis of macrolide antibiotics, is unusual in that it requires an additional protein partner, DesVIII, for its full activity. The level of substrate tolerance of the DesVII/DesVIII pair was explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
59
0
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 72 publications
1
59
0
5
Order By: Relevance
“…Previously, it was shown that the activation of some glycosyltransferases depends upon their interactions with auxiliary proteins. One glycosyltransferase, DesVII, which is involved in the biosynthesis of the macrolide antibiotics methymycin and pikromycin in Streptomyces venezuelae, was only activated if an auxiliary protein, DesVIII, was present (36)(37)(38). Similarly, other glycosyltransferases have been found to require another auxiliary protein for their activity (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was shown that the activation of some glycosyltransferases depends upon their interactions with auxiliary proteins. One glycosyltransferase, DesVII, which is involved in the biosynthesis of the macrolide antibiotics methymycin and pikromycin in Streptomyces venezuelae, was only activated if an auxiliary protein, DesVIII, was present (36)(37)(38). Similarly, other glycosyltransferases have been found to require another auxiliary protein for their activity (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Activity of the glycosyltransferase EryCIII, which is required for biosynthesis of the antibiotic erythromycin D, is dependent upon an auxiliary protein, EryCII (43). Although the roles of these auxiliary proteins are not clear, it has been proposed that these auxiliary proteins are required to induce conformational changes of the glycosyltransferases, which consequently activate these enzymes (36,42).…”
Section: Discussionmentioning
confidence: 99%
“…This was determined during the study of DesVII, a glycosyltransferase that catalyzes the attachment of desosamine onto 12-and 14-membered macrolactone rings during the biosynthesis of the macrolide antibiotics methymycin and pikromycin in Streptomyces venezuelae. For glycosylation to proceed efficiently, the presence of an auxiliary protein, DesVIII, was found to be necessary in vivo as well as in vitro (2,3,12,13). Since the discovery of the role of DesVIII in glycosylation, other pairs of glycosyltransferases and auxiliary proteins have been identified and characterized, and most of these are involved in macrolide biosynthesis (14,24,25).…”
mentioning
confidence: 99%
“…Indeed, it has been observed that the auxiliary protein is required for the initial activation of the glycosyltransferase, but then the activated glycosyltransferase can catalyze the glycosyltransfer alone. It was thus proposed that auxiliary proteins induce a one-time conformational change of the glycosyltransferase to its active form (2).…”
mentioning
confidence: 99%
“…Among several well-known actinomycete heterologous hosts, a pikromycin (Pik)/methymycin-producing strain, Streptomyces venezuelae ATCC 15439, has recently been developed as a promising host in that it is amenable to genetic manipulation and requires a short culture period (3 to 4 days) for metabolite production compared to other Streptomyces species (7,8,19,23,24). In addition, the presence of two post-polyketide synthase (PKS) tailoring enzymes that have unusual substrate flexibility, DesVII glycosyltransferase (2,3,6,25) and PikC P450 monooxygenase (11,13,18), offers it another advantage as a heterologous host for combinatorial biosynthesis of novel compounds. However, one of the key challenges in developing S. venezuelae as a competent heterologous host is the relatively low production of heterologous polyketides (8).…”
mentioning
confidence: 99%